Preventive aspects and dental social actions in the non-governmental organization Casa Menina Mulher - Municipality of Recife, state of Pernambuco (PE) (Research, Society and Development, 2024)
Objective: To report the social actions carried out by students of the basic dentistry course at the Recife School of Dentistry (FOR), aimed at vulnerable residents, under a service regime guaranteed by the Statute of Children and Adolescents (ECA). The actions are part of the Extension of the aforementioned school. Methodology: Ten (10) social actions were carried out in an extension nature to protect vulnerable people, coordinated with the director and coordinators of the institution, to then bring the undergraduate students to hold educational lectures, record the index of caries and gum and periodontal disease, and instruction on brushing and flossing techniques, with the distribution of brushing and brushing kits, as well as the oral records of all residents through odontograms and clinical records for bacterial plaque control based on the Silness and Löe Plaque Index (1964). Results: The girls living in the institution learned the basics of cariogenic foods and their relationship with inappropriate brushing or even lack of oral hygiene, and most managed to go from a scale of 3 to 1, demonstrating learning about the content learned. Conclusion: The social actions promoted by the students of the Dentistry course at FOR demonstrated significant effectiveness in promoting oral health among residents in vulnerable situations. Through an extensionist approach, it was possible not only to educate the participants about oral hygiene and nutrition practices, but also to monitor oral health systematically.